A photosensitizer, a suture comprising the same, and a preparation method thereof
Patent Information
- Application Number
- CN202511221175.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-29
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2045-08-29
AI Technical Summary
[0003]针对上述现有技术涉及的光敏剂无法对缝合线进行降解调控的缺陷,本发明将提供一种光敏剂、包括其的缝合线及其制备方法和应用
[0013]以分子量已知的聚苯乙烯为参照品,以及以体积百分数为5%氯仿和体积百分数为95%的四氢呋喃为流动相,在检测器为2414RI(折光指数)检测器下采用凝胶渗透色谱(GPC)测试聚乳酸的数均分子量。
Smart Images

Figure BDA0005571449810000021 
Figure BDA0005571449810000022 
Figure BDA0005571449810000031
Abstract
Description
Technical Field
[0001] This invention belongs to the field of sutures, specifically relating to a photosensitizer, a suture including the photosensitizer, and a method for preparing the same. Background Technology
[0002] Sutures are widely used in all aspects of clinical surgery, playing a crucial role in promoting wound healing. In clinical settings, besides requiring good antibacterial properties to prevent infection, real-time monitoring of suture biodegradability is equally important. Using biodegradable sutures can avoid the problem of suture removal during wound healing. Furthermore, suture degradation is closely related to the wound healing process; monitoring the degradation status helps doctors predict the degree of wound healing. Given the different healing time requirements of different tissues and individual differences, sutures with precisely controllable degradation times are needed. Currently, photosensitizers are loaded onto the suture surface, allowing for suture tracking through photosensitizer detection and visualization. The loading methods are mainly impregnation / adsorption or coating. However, a thick photosensitizer coating significantly affects the suture diameter, making it unsuitable for fine sutures and limiting its application. Impregnation / adsorption relies on adsorption, which is prone to uneven adsorption. Moreover, whether coating or adsorption, the interaction between the photosensitizer and the large suture surface is not strong enough or uniform, easily leading to desorption. Additionally, the photosensitizer only remains on the suture surface and cannot regulate suture degradation. Summary of the Invention
[0003] In view of the shortcomings of the photosensitizers in the prior art that cannot regulate the degradation of sutures, the present invention will provide a photosensitizer, a suture including the photosensitizer, a method for preparing the photosensitizer, and its application.
[0004] To achieve the above objectives, the following technical solutions are specifically included:
[0005] On the one hand, the present invention provides a photosensitizer, the chemical structural formula of which is shown in Formula I below:
[0006]
[0007] n represents the degree of aggregation, which is a positive integer between 10 and 400.
[0008] This invention utilizes 1-(3-aminopropyl)-4-[4-(diphenylamino)styryl]-pyridinium bromide (TVP-A) as a grafting group to the end of a polylactic acid (PLA) molecular chain to obtain the photosensitizer of this invention. The TVP-A group on this photosensitizer has a donor-acceptor (DA) structure, including triphenylamine (D), a carbon-carbon double bond (π-bridge), and a pyridine (A) moiety. This allows the photosensitizer to generate reactive oxygen species (ROS) to kill bacteria, fungi, and other microorganisms without causing cell damage. It exhibits toxicity or drug resistance; it can also emit fluorescence, thereby enabling the monitoring of the position and state of photosensitizers to achieve fluorescence imaging; its pyridine moiety also carries a quaternary ammonium salt structure, giving the photosensitizer a positive charge, making it easier to capture and kill negatively charged bacteria; a primary amino terminus is also coupled to the pyridine, which can be grafted onto the carboxyl terminus of the PLA chain segment as an active functional group, making the photosensitizing PLA more easily bind to biodegradable polyester suture matrix; in addition, it also has good biocompatibility.
[0009] Preferably, n is a positive integer between 27 and 280.
[0010] Preferably, the photosensitizer is obtained by grafting TVP-A onto polylactic acid-active ester. The number average molecular weight of the polylactic acid-active ester is 2000-20000 Da, specifically 2000, 5000, 8000, 11000, 14000, 17000, 20000 Da, etc., and specific values between the above ranges. Due to space limitations and for the sake of brevity, this invention will not exhaustively list all the specific values included in the range. The chemical structure of TVP-A is shown in Formula II below:
[0011]
[0012]
[0013] Using polystyrene with a known molecular weight as a reference, and with 5% chloroform and 95% tetrahydrofuran as mobile phases, the number-average molecular weight of polylactic acid was determined by gel permeation chromatography (GPC) under a 2414RI (refractive index) detector.
[0014] In a second aspect, the present invention provides a suture, comprising a matrix and the photosensitizer.
[0015] The photosensitizer of this invention contains PLA segments, enabling it to be more uniformly and firmly distributed inside and outside the suture. The photosensitizer exhibits fluorescence properties, providing the suture with stable fluorescence imaging capabilities, facilitating suture monitoring and tracking. Furthermore, on one hand, by applying light to the suture, the photosensitizer generates reactive oxygen species (ROS) for antibacterial and direct degradation of the suture matrix, achieving both antibacterial and photodynamic-accelerated suture degradation functions. On the other hand, because the photosensitizer is uniformly distributed inside and outside the suture, it also allows for the generation of reactive oxygen species (ROS) within the suture, accelerating its degradation while simultaneously speeding up the penetration of water molecules into the suture's interior, promoting the hydrolysis of the suture matrix itself, and further accelerating suture degradation. In summary, the timing and rate of suture degradation can be controlled by adjusting the timing and duration of light application to the suture.
[0016] Preferably, the photosensitizer in the suture has a mass percentage content of 0.5%-2%, specifically 0.5%, 0.7%, 0.9%, 1.1%, 1.3%, 1.5%, 1.7%, 1.9%, 2.0%, etc., as well as specific values between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values included in the range.
[0017] Preferably, the average diameter of the wire substrate is 0.1-1.3 mm, specifically 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3 mm, etc., as well as specific point values between the above values. Due to space limitations and for the sake of brevity, this invention will not exhaustively list the specific point values included in the range.
[0018] Preferably, the matrix material includes at least one of polylactic acid (PLA), polylactic acid-glycolic acid copolymer (PLGA), or polyglycolic acid (PGA).
[0019] Preferably, the number-average molecular weight of the matrix is 50,000 Da to 160,000 Da, specifically 50,000, 70,000, 90,000, 110,000, 130,000, 150,000, 160,000 Da, and other specific values between the above values. Due to space limitations and for the sake of brevity, this invention will not exhaustively list all the specific values included in the range. The molecular weight is tested using GPC testing.
[0020] Thirdly, the present invention provides a method for preparing the aforementioned suture, comprising the following steps:
[0021] S1. TVP-A and polylactic acid-active ester (PLA-NHS) are dissolved in chloroform and reacted. The mixture is then precipitated in ethanol, filtered, washed and lyophilized to obtain the photosensitizer.
[0022] S2. The suture base material and the photosensitizer are mixed and melt-spun sequentially to obtain the suture.
[0023] The present invention obtains the suture by melt spinning photosensitizer and matrix raw material, which is beneficial to uniformly distribute photosensitizing groups inside and on the outer surface of the suture, and is more conducive to regulating its degradation process.
[0024] Preferably, in step S1, the mass ratio of TVP-A to polylactic acid-active ester is 1:(2-8).
[0025] Preferably, in step S2, the temperature of the melt spinning is 170-250°C.
[0026] Preferably, in step S2, the mass ratio of the matrix material of the suture to the photosensitizer is (99.5-98):(0.5-2).
[0027] Compared with the prior art, the present invention has the following advantages: the photosensitizer of the present invention carries PLA segments, which can make it more uniform and firm in its distribution inside and outside the biodegradable polyester suture; the photosensitizer has fluorescent properties, giving the suture a stable fluorescent imaging function, which facilitates the monitoring and tracking of the suture; moreover, the degradation timing and degradation rate of the suture can be controlled by controlling the timing and time of light application to the suture. Attached Figure Description
[0028] Figure 1 This is a synthesis route diagram for the TVP-PLA of the present invention.
[0029] Figure 2 This is a synthetic route diagram for compound 1, an intermediate product in the synthesis of TVP.
[0030] Figure 3 This is a synthetic route for synthesizing TVP-A from intermediate compound 1. Detailed Implementation
[0031] To better illustrate the purpose, technical solution, and advantages of the present invention, specific embodiments will be used to further explain the invention below. Unless otherwise specified, all raw materials used in the embodiments and comparative examples of the present invention are commercially available, and the same raw materials were used in all parallel experiments.
[0032] (1) PLA:
[0033] PLA-1: PLAFY802, molecular weight 145000Da, purchased from Anhui Fengyuan Biotechnology Co., Ltd.
[0034] PLA-2: PLAFY601, molecular weight 106000 Da, purchased from Anhui Fengyuan Biotechnology Co., Ltd.
[0035] PLA-3: PLA FY201, molecular weight 81000Da, purchased from Anhui Fengyuan Biotechnology Co., Ltd.
[0036] (2) PLGA: RESERMORER GL 903S, molecular weight 115000 Da, purchased from Evonik Specialty Chemicals (Shanghai) Co., Ltd.;
[0037] (3) PGA: RESERMORER G 205S, molecular weight 152000 Da, purchased from Evonik Specialty Chemicals (Shanghai) Co., Ltd.;
[0038] (4) Polylactic acid-active ester (PLA-NHS):
[0039] PLA-NHS-1: R-PL1203-1 from Xi'an Ruixi Biotechnology Co., Ltd., with a number-average molecular weight of 2000;
[0040] PLA-NHS-2: R-PL1203-2 from Xi'an Ruixi Biotechnology Co., Ltd., with a number-average molecular weight of 10,000;
[0041] PLA-NHS-3: R-PL1203-3 from Xi'an Ruixi Biotechnology Co., Ltd., with a number-average molecular weight of 20,000;
[0042] (5) The molecular weight of TVP-A is 486.5 Da, and the chemical formula of TVP-A is shown in Formula II below:
[0043]
[0044] A schematic diagram of the TVP-A synthesis route is shown below. Figure 2-3 As shown, the specific steps include the following:
[0045] S1. In a 50 mL two-necked flask, add 10 mL of N,N-dimethylformamide (DMF), 4-methylpyridine (10.1 mmol), and potassium tert-butoxide (t-BuOK, 2.0 mmol). After stirring for 30 minutes under nitrogen protection at room temperature, add 4-formyltriphenylamine (5.05 mmol) and stir overnight at room temperature. Then quench the reaction with 20 mL of saturated brine, extract with ethyl acetate and saturated brine solution, evaporate the crude product to dryness, and perform column chromatography (eluent is a mixed solvent of ethyl acetate:n-hexane = 1:6, v / v) to give a yellow solid compound 1.
[0046] S2. In a 50 mL two-necked flask, add 10 mL of acetonitrile, compound 1 (0.58 mmol), and 3-bromopropylamine hydrobromic acid (0.87 mmol). Stir at room temperature for 1 hour, then heat under reflux overnight. Precipitate the crude product with 20 mL of ethyl acetate. Perform alumina column chromatography on the crude product (eluent is a mixed solvent of dichloromethane:methanol = 98:2, v / v) to give product TVP-A, which is a red solid. 1 H NMR(Bruker Avance,400MHz,CD3OD),δ(ppm):8.73-8.71(m,2H),8.10(m,2H),7.90(m,1H),7.62-7.59(m,2H),7.36-7.32(m,4H),7.27-7 .23(m,1.5H),7.17-7.12(m,6H),7.00-6.98(m,2.5H),4.57-4.52(m,2H),2.74-2.70(m,2H),2.14-2.10(m,2H),1.29(s,2H). HRMS(EI):calculated for C 28 H 28 BrN3[M - Br] + :406.2278; found:406.2301.
[0047] (6) TVP-PLA:
[0048] The preparation method of TVP-PLA includes the following steps:
[0049] 20g of TVP-A and 100g of PLA-NHS (molecular weight 2000-20000 Da) were dissolved in 10L of chloroform solvent and reacted at 37℃ for 12h with stirring. The mixture was then precipitated in anhydrous ethanol, filtered, and subsequently washed three times with anhydrous ethanol and three times with pure water to remove excess TVP-A and small molecule byproducts. Finally, the product was freeze-dried under vacuum to obtain the photosensitizer powder, denoted as TVP-PLA. The synthetic route is as follows: Figure 1 As shown, the chemical structure of TVP-PLA is as follows:
[0050]
[0051] n represents the degree of aggregation, which is a positive integer between 27 and 280.
[0052] With the same mass ratio of TVP-A and PLA-NHS, different molecular weights of TVP-PLA can be obtained by changing the molecular weight of PLA-NHS, as shown in Table 1.
[0053] Table 1
[0054]
[0055]
[0056] Examples 1-9
[0057] A suture, the preparation method of which includes the following steps:
[0058] Pre-dried TVP-PLA was mixed evenly with PLA chips, and then the mixture was poured into a single-screw extruder for melt spinning. The spinning zone temperatures were 215, 210, 210, 195, and 175°C. By adjusting the die diameter range, metering pump, and drawing process, monofilament sutures with a diameter of 0.1 mm were prepared.
[0059] When spinning with PGA and PGLA as the matrix, refer to the above method. When spinning with PGA as the matrix, the spinning temperature of each zone is 245℃, 240℃, 240℃, 225℃, and 200℃; when spinning with PGLA as the matrix, the spinning temperature of each zone is 235℃, 230℃, 230℃, 210℃, and 190℃.
[0060] The specific information on raw materials is shown in Table 2.
[0061] Comparative Example 1
[0062] Compared with Example 2, this comparative example used 0.1mm monofilament PLA-2 suture as the final suture for performance testing. The specific steps are as follows:
[0063] 100 parts by weight of PLA-2 chips were poured into a single-screw extruder for melt spinning. The spinning zone temperatures were 215℃, 210℃, 210℃, 195℃, and 175℃. By adjusting the die diameter range, metering pump, and drawing process, monofilament sutures with a diameter of 0.1 mm were prepared.
[0064] Comparative Example 2
[0065] Compared with Example 2, this comparative example directly uses TVP-A and PLA-2 as raw materials to prepare sutures. The specific steps are as follows:
[0066] One part by weight of pre-dried TVP-A was mixed evenly with 99 parts by weight of PLA-2 chips. The mixture was then poured into a single-screw extruder for melt spinning. The spinning zones were 215, 210, 210, 195, and 175°C. By adjusting the die diameter range, metering pump, and drawing process, monofilament sutures with a diameter of 0.1 mm were prepared. Comparative Example 3
[0067] Compared with Example 2, this comparative example directly uses an impregnation method to prepare the suture. The specific steps are as follows:
[0068] PLA-2 sutures with a diameter of 0.1 mm were placed in a 30% chloroform (chloroform: ethanol = 3:7) dispersion of TVP-PLA-2 at a concentration of 10 g / L and soaked in a shaker at 37°C and 220 rpm for 1 hour. After vacuum drying, they were weighed. The soaking and drying were repeated several times until the PLA-2 sutures gained 1% in weight, thus obtaining coated sutures.
[0069] Table 2 (parts by weight)
[0070]
[0071] (1) Fluorescence properties:
[0072] The sutures of Examples 1-9 can be excited with a blue light source of approximately 450-490 nm, and a fluorescence imaging device collects strong fluorescence signals in the green channel of approximately 530-590 nm. This confirms that the photosensitizer of the present invention successfully binds to the suture matrix, and that the photosensitizer imparts effective fluorescence information to the suture, facilitating the monitoring of the suture's position and condition for fluorescence imaging and detection.
[0073] (2) Antibacterial properties:
[0074] To investigate the antibacterial properties of the suture, a 10 cm long suture was placed in a 24-well plate, and 10 μL of bacterial suspension (1×10⁻⁶) was dropped onto its surface. 6 CFU / mL). The sample was incubated in the dark at 37°C for 30 minutes and then exposed to white light (50 mW / cm²). 2 Irradiate for 10 or 20 minutes. Then, dilute the bacterial suspension and spread it onto agar plates. The antibacterial activity of the suture is determined by counting the number of colonies on the agar plates.
[0075] Antibacterial activity was evaluated by the inhibition rate, calculated using the following formula: Inhibition rate = [1 - (number of colonies in the treated group (i.e., inhibitory agent) / number of colonies in the blank group)] × 100. The *Escherichia coli* (ATCC 8739) used in the antibacterial test was obtained from the Guangdong Provincial Microbial Culture Collection Center.
[0076] The test results are shown in Table 3.
[0077] Table 3
[0078] Comparative Example 1 0 Comparative Example 2 50 Comparative Example 3 99.5 Example 1 99 Example 2 99 Example 3 99 Example 4 99 Example 5 99 Example 6 99.5 Example 7 98 Example 8 98 Example 9 99.5
[0079] Comparative Example 1 contained no photosensitizer and had no antibacterial effect; Comparative Example 2 directly extruded a blend of photosensitizer TVP-A and PLA, resulting in uneven dispersion of TVP-A and weak antibacterial effect; Comparative Example 3 had a large amount of TVP-PLA loaded on its surface, exhibiting the strongest antibacterial effect. In Example 3, TVP-PLA was uniformly dispersed inside and outside the suture, demonstrating a good antibacterial effect.
[0080] (3) Degradation performance test:
[0081] (a) Weekly light or dark treatment: Immerse 10 mg of suture in Sorensen phosphate buffer (pH 7.4) in a glass bottle and incubate at 37°C in the dark using a shaker. Weekly, remove the bottle containing the suture and place it under white light (50 mW / cm²). 2 After 1 hour of light exposure (i.e., once a week), remove the suture from the buffer solution, rinse with deionized water, and vacuum dry at 37°C. Weigh the dried suture. If the residual weight of the suture is greater than 1 mg, return it to the buffer solution and incubate at 37°C on a shaker, waiting for the next week's light exposure and weighing. Repeat this cycle until the residual weight of the suture is less than or equal to 1 mg, at which point the experiment is terminated, and the suture has degraded by more than 90%. Record the number of weeks required for the suture to degrade by more than 90%.
[0082] (b) Daily light exposure: Immerse 10 mg of suture in Sorensen phosphate buffer (pH 7.4) in a glass bottle and incubate at 37°C in the dark using a shaker. Each day, remove the bottle containing the suture and place it under white light (50 mW / cm²). 2 After 1 hour of light exposure (considered one light exposure), the sutures were returned to the 37°C shaker for incubation, awaiting the next day's light treatment. This process was repeated until the set number of light exposures was reached, at which point the light treatment was terminated. After termination of light treatment, the sutures were removed from the buffer solution weekly, rinsed in deionized water, and then vacuum-dried at 37°C. The weight of the dried sutures was measured. If the residual weight of the sutures was greater than 1 mg, they were returned to the buffer solution and incubated in the dark at 37°C. This cycle was repeated until the residual weight of the sutures was less than or equal to 1 mg, at which point the experiment was terminated, indicating that the sutures had degraded by more than 90%. The total number of light exposures and the number of weeks required for the sutures to degrade by more than 90% were recorded.
[0083] (c) Random light exposure for 14 days: 10 mg of suture was immersed in Sorensen phosphate buffer (pH 7.4) in a glass bottle and incubated in a shaker at 37°C in the dark. During the first 6 weeks, the bottle containing the suture was randomly selected and placed under white light (50 mW / cm²) for 14 days each day. 2After 1 hour of light exposure (considered one light exposure), the sutures were returned to the 37°C shaker for incubation, awaiting the next day's light treatment. The remaining time was spent in darkness. Starting from week 7, the sutures were removed from the buffer solution weekly, rinsed in deionized water, and then vacuum-dried at 37°C. The weight of the dried sutures was measured. If the residual weight of the sutures was greater than 1 mg, they were returned to the buffer solution and incubated in the dark at 37°C. This cycle was repeated until the residual weight of the sutures was less than or equal to 1 mg. At this point, the experiment was terminated, indicating that the sutures had degraded by more than 90%. The number of weeks required for the sutures to degrade by more than 90% was recorded.
[0084] If the suture is observed to have been in place for more than 51 weeks and its degradation rate has not yet reached 90%, the degradation period is too long and clearly does not meet the requirements. The test and recording can be stopped.
[0085] Table 4
[0086]
[0087]
[0088] In Comparative Example 1, the simple PLA monofilaments were highly crystalline, and hydrolysis only occurred in the amorphous regions where water molecules could easily penetrate. Hydrolysis was slow, and no significant quality decrease was observed even after more than 51 weeks. In the suture of Comparative Example 2, the photosensitizer TVP-A was dispersed inside the PLA monofilaments, but the dispersion was uneven. A certain degree of photodynamic activity promoted PLA decomposition, reducing the time required for 90% decomposition of the suture to 45 weeks. Meanwhile, in the suture of Comparative Example 3, because the photosensitizer was only adsorbed on the surface of the PLA suture, its effect on the decomposition rate of deeper PLA was limited by the lifetime and diffusion distance of ROS, and the time required for 90% decomposition of the suture exceeded 51 weeks.
[0089] In Examples 1-9, the TVP-PLA photosensitive groups in the sutures were more uniformly dispersed, and the decomposition cycle of the sutures was significantly reduced to less than 30 weeks. This is due, on the one hand, to the direct decomposition of PLA by the ROS generated by the presence of TVP-PLA; and on the other hand, the decomposition of the sutures promoted the penetration of water molecules into deeper tissues, thus significantly accelerating the decomposition process. Furthermore, continuous daily illumination further shortened the degradation time compared to continuous weekly illumination. Therefore, the illumination frequency can be adjusted as needed to achieve controllable degradation rates.
[0090] Examples 1-3 demonstrate that the molecular weight of the PLA matrix in sutures also affects the degradation rate; the smaller the PLA molecular weight, the faster the degradation rate. Furthermore, the timing of light exposure can be selected as needed to control the degradation rate and duration of the sutures. Daily random light exposure experiments in Examples 1-3 show that earlier light exposure results in faster suture degradation than later light exposure. This is because earlier light exposure further accelerates the penetration of water molecules into the PLA, promoting the hydrolysis of PLA itself and further increasing the degradation rate of the sutures.
[0091] Examples 4-5 show that, compared with PLA as the matrix, the degradation rate of sutures is greater when PLGA and PGA are used as the matrix.
[0092] As can be seen from Examples 2 and 6-7, the smaller the molecular weight of the PLA molecular chain portion (obtained from the reaction of PLA-NHS raw materials) in the photosensitizer TVP-PLA, the faster the degradation rate of the suture.
[0093] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. A photosensitizer, characterized in that, Its chemical structural formula is shown in Formula I below: n represents the degree of aggregation, which is a positive integer between 10 and 400.
2. The photosensitizer as described in claim 1, characterized in that, The photosensitizer is obtained by grafting TVP-A onto polylactic acid-active ester, wherein the number-average molecular weight of the polylactic acid-active ester is 2000-20000 Da; the chemical structure of the TVP-A is shown in Formula II below:
3. A suture, characterized in that, Includes the matrix and the photosensitizer as described in claim 1 or 2.
4. The suture as described in claim 3, characterized in that, The photosensitizer in the suture has a mass percentage content of 0.5%-2%.
5. The suture as described in claim 3, characterized in that, The average diameter of the suture is 0.1-1.3 mm.
6. The suture as described in claim 3, characterized in that, The matrix material includes at least one of polylactic acid, polylactic acid-glycolic acid copolymer, or polyglycolic acid.
7. The suture as described in claim 3, characterized in that, The number-average molecular weight of the matrix is 50,000 Da to 160,000 Da.
8. A method for preparing the suture according to any one of claims 3-7, characterized in that, Includes the following steps: S1. TVP-A and polylactic acid-active ester are dissolved in chloroform and reacted. Then, the mixture is precipitated in ethanol, filtered, washed, and freeze-dried to obtain the photosensitizer. S2. The suture base material and the photosensitizer are mixed and melt-spun sequentially to obtain the suture.
9. The method for preparing the suture as described in claim 8, characterized in that, In step S2, the mass ratio of the matrix material of the suture to the photosensitizer is (99.5-98):(0.5-2).
Citation Information
Patent Citations
Antibacterial surgical suture as well as preparation method and application thereof
CN115839028A
AIE functionalized synergistic antibacterial modified polysaccharide material as well as preparation method and application thereof
CN116199801A
